2003
DOI: 10.1067/mva.2003.232
|View full text |Cite
|
Sign up to set email alerts
|

Small popliteal artery aneurysms: Are they clinically significant?

Abstract: Smaller popliteal artery aneurysm was associated with higher incidence of thrombosis, clinical symptoms, and distal occlusive disease. Liberal use of duplex scanning in this setting may have accounted for the increased awareness that small popliteal artery aneurysms can thrombose and present with severe ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 12 publications
0
47
0
2
Order By: Relevance
“…3,5,[7][8][9][10][11][12][13][14][15]20,24,[26][27][28][31][32][33][34][35][36][37] In the majority of patients, the endovascular repair was done in the presence of a good tibial run-off; at least two patent tibial arteries were present in 71% (95% CI 65%-76%) of patients. 1,7,10,[12][13][14][15]24,27,32,33,35,38 Several types of stents have been used to treat PAA. At the beginning of the era of this new modality of treatment, in North America home-made devices made of balloon expandable stents covered with vein or PTFE were used, while in Europe the Cragg Endo Pro stents were used, which included the System 1 (a self expandable nitinol stent covered by polyester fabric, Cragg EndoPro System; Mintec, La Ciotat, France); the Passager stent graft (a self expandable, polyester-covered metal stent-grafts; Boston Scientific, Watertown, Mass), and the Corvita stentgraft (a metallic self-expandable, braided wire stent to which is bonded an inner liner of polycarbonate urethane microfibers; Boston Scientific, Bülach, Switzerland).…”
Section: Resultsmentioning
confidence: 99%
“…3,5,[7][8][9][10][11][12][13][14][15]20,24,[26][27][28][31][32][33][34][35][36][37] In the majority of patients, the endovascular repair was done in the presence of a good tibial run-off; at least two patent tibial arteries were present in 71% (95% CI 65%-76%) of patients. 1,7,10,[12][13][14][15]24,27,32,33,35,38 Several types of stents have been used to treat PAA. At the beginning of the era of this new modality of treatment, in North America home-made devices made of balloon expandable stents covered with vein or PTFE were used, while in Europe the Cragg Endo Pro stents were used, which included the System 1 (a self expandable nitinol stent covered by polyester fabric, Cragg EndoPro System; Mintec, La Ciotat, France); the Passager stent graft (a self expandable, polyester-covered metal stent-grafts; Boston Scientific, Watertown, Mass), and the Corvita stentgraft (a metallic self-expandable, braided wire stent to which is bonded an inner liner of polycarbonate urethane microfibers; Boston Scientific, Bülach, Switzerland).…”
Section: Resultsmentioning
confidence: 99%
“…However, we have reported the incidence of thrombosis even in smaller aneurysms. 9 Ramesh et al 10 observed distortion of the aneurysm as a sensitive predictor of thrombosis in PAA rather than the size alone. These authors proposed aneurysms with a combination of distortion, and size of more than 3 cm are more likely to undergo thrombosis.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, we have reported the incidence of thrombosis even in smaller aneurysms. 9 Ramesh et al 10 observed distortion of the aneurysm as a more sensitive predictor of thrombosis in PAA than size alone. These authors proposed that aneurysms with a combination of distortion and size of more than 3 cm are more likely to undergo thrombosis.…”
Section: Discussionmentioning
confidence: 98%